Chimeric Allografts Induced by Short‐Term Treatment With Stem Cell Mobilizing Agents Result in Long‐Term Kidney Transplant Survival Without Immunosuppression: II, Study in Miniature Swine. Issue 7 (22nd March 2016) - Cameron, A. M.; Wesson, R. N.; Ahmadi, A. R.; Singer, A. L.; Hu, X.; Okabayashi, T.; Wang, Y.; Shigoka, M.; Fu, Y.; Gao, W.; Raccusen, L. C.; Montgomery, R. A.; et al.
Abstract : Transplantation is now lifesaving therapy for patients with end‐stage organ failure but requires lifelong immunosuppression with resultant morbidity. Current immunosuppressive strategies inhibit T cell activation and prevent donor–recipient engagement. Therefore, it is not surprising that few host cells are demonstrated in donor grafts. However, our recent small animal studies found large numbers of recipient stem cells present after transplantation and pharmacological mobilization, resulting in a chimeric, repopulated organ. We now confirm these findings in a well‐characterized large animal preclinical model. Here, we show that AMD3100 and FK506 mobilization of endogenous stem cells immediately post kidney transplantation combined with repeat therapy at 1, 2, and 3 months led to drug‐free long‐term survival in maximally immunologically mismatched swine. Three long‐term recipients have stable chimeric transplants, preserved antidonor skin graft responses, and normal serum creatinine levels despite withdrawal of all medication for 3 years. Abstract : In maximally immunologically mismatched swine, short‐term treatment with AMD3100 plus low‐dose FK506 and repeat dosing result in chimeric kidney allografts and immunosuppression‐free long‐term survival. See the companion article onpage 2055 .